Novel Cecropin-4 Derived Peptides against Methicillin-Resistant Staphylococcus aureus - Jian Peng; Biswajit Mishra; Rajamohammed Khader; LewisOscar Felix; Eleftherios Mylonakis (Antibiotics, 2021)
Increasing microbial resistance, coupled with a lack of new antimicrobial discovery, has led researchers to refocus on antimicrobial peptides (AMPs) as novel therapeutic candidates. Significantly, the less toxic cecropins have gained widespread attention for potential antibacterial agent development. However, the narrow activity spectrum and long sequence remain the primary limitations of this approach. In this study, we truncated and modified cecropin 4 (41 amino acids) by varying the charge and hydrophobicity balance to obtain smaller AMPs. The derivative peptide C18 (16 amino acids) demonstrated high antibacterial activity against Gram-negative and Gram-positive bacteria, as well as yeasts. Moreover, C18 demonstrated a minimal inhibitory concentration (MIC) of 4 µg/mL against the methicillin-resistant Staphylococcus aureus (MRSA) and showed synergy with daptomycin with a fractional inhibition concentration index (FICI) value of 0.313. Similar to traditional cecropins, C18 altered the membrane potential, increased fluidity, and caused membrane breakage at 32 µg/mL. Importantly, C18 eliminated 99% persisters at 10 × MIC within 20 min and reduced the biofilm adherence by ~40% and 35% at 32 and 16 µg/mL. Besides, C18 possessed a strong binding ability with DNA at 7.8 μM and down-regulated the expression of virulence factor genes like agrA, fnb-A, and clf-1 by more than 5-fold (p < 0.05). Interestingly, in the Galleria mellonella model, C18 rescued more than 80% of larva infected with the MRSA throughout 120-h post-infection at a single dose of 8 mg/kg (p < 0.05). In conclusion, this study provides a reference for the transformation of cecropin to derive small peptides and presents C18 as an attractive therapeutic candidate to be developed to treat severe MRSA infections.